Metacarpal index in Nigerian Adults and children. (2002)
The metacarpal index(MI) is used in screening for patients with arachnodactyly especially Marfan's syndrome. It is a radiographic measure of the slenderness of the 2nd-5th metacarpals, which was measured in a total of 608 Nigerians of which 55 (9%) were childrens and 553(91%) were adults. The study shows that the MI increases steadily in children approaching the adult value at about the age of 9 years in females and 13 years in males coinciding with menarche and puberty respectively. A metacarpal index of up to 11 can be considered to be within normal limits for a Nigeria adult. In both children and adults, the MI was found to be higher in females than in males. In both sexes the metacarpal index for the left hand in the adult subjects is generally higher than that of the right hand, but in children, no significant difference is observed. As in other Africans, Nigerian adults have a higher MI than caucasians.